Nutritional status and morbidity pattern in school age children in Nepal - Bhandari, N; Shrestha, GK (Journal of College of Medical Sciences-Nepal, 2012)
School Health has been regarded as a high priority intervention in developing countries. However it has not been prioritized in Nepal for many years. The objectives of the study are to find out the nutritional status and morbidity pattern in school age children. To arouse importance of personal hygiene and healthful surrounding through information, education and communication (IEC). This cross-sectional study was administered in two schools located in Bolde phedeche and Mahure of Kavrepalanchowk. From the selected schools, a total number of 160 students studying from Grade 1 to V were enumerated in the study using census survey method. Among 160 students, the most important three problems were pediculosis 42(26.2 %), dental caries 29(18.1%), and waxy ear 27(17.1 %). Thus the school health education should put more emphasis on oral care, nutrition, personal hygiene and others. Applying classification of Indian Academy of Pediatrics: based on weight for age, 36(55.3%) boys and 34(35.8%) girls fall under 1st degree malnutrition and 15(23.07%) boys and 44(46.3%) girls fall under IInd degree malnutrition, 7(7.2 %) girls fall under IIIrd degree malnutrition.The health and nutritional standards of school children in this study were found to be unsatisfactory. Among different morbidity pediculosis is found more in girls. The present study put more emphasis on the need for initiation of school health program in the school with more on improving personal hygiene, prevention of disease like parasitic infection/infestation and improvement of their nutritional status. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-2, 12-16 DOI: http://dx.doi.org/10.3126/jcmsn.v8i2.6832